H Hubungan Peran Orang Tua Dengan Sikap Remaja Usia 15 19 Tahun Dalam Mengambil Keputusan Pernikahan Dini Di SMKN 2 Simpang Empat Tahun 2021: THE CORRELATIONS BETWEEN SOCIAL FACTORS (ROLES) WITH THE ATTITUDE OF ADOLESCENTS AGED 15-19 YEARS IN MAKING DECISIONS TO MARRY YOUNG AT SMKN 2 SIMPANG EMPAT TAHUN IN 2021 - Farhandika Putra (LPPM Universitas Sari Mulia, 2022)
Background: Early marriage is an underage marriage whose preparation target has not been said to be maximal. Objective: The aim of this study was to determine the correlations between social factors (roles) with the attitude of adolescents aged 15-19 years in making decisions to marry young. Method: The design of this study was a quantitative design with cross sectional. The sample in this study were 100 respondents with simple random sampling technique. Result: The results of this study indicated that were 60 respondents (60%) had positive social factors (roles), and 56 respondents (56%) had positive attitudes. Analysis by using Chi Square test obtained sig 0.007 (<0.05). Conclusion: The conclusion of this study, there is a correlations between social factors (roles) with adolescent attitudes in making decisions to marry young. It was recommended that the SMKN 2 Simpang Empat can increase students' knowledge about the effects of young marriage by providing education as a prevention effort for young marriage.